Dissociated vacancies and screw dislocations in MgO and UO2: atomistic modeling and linear elasticity analysis - Xiang-Yang Liu (Nature Portfolio, 2019)
Abstract Understanding the effect of dislocations on the mass transport in ionic ceramics is important for understanding the behavior of these materials in a variety of contexts. In particular, the dissociated nature of vacancies at screw dislocations, or more generally, at a wide range of low-angle twist grain-boundaries, has ramifications for the mechanism of defect migration and thus mass transport at these microstructural features. In this paper, a systematic study of the dissociated vacancies at screw dislocations in MgO is carried out. The important role of stress migration in the atomistic modeling study is identified. Another aspect of the current work is a rigorous treatment of the linear elasticity model. As a result, good agreement between the atomistic modeling results and the linear elasticity model is obtained. Furthermore, we demonstrate that the proposed vacancy dissociation mechanism can also be extended to more complicated ionic ceramics such as UO2, highlighting the generality of the mechanism.